Assisted voluntary return schemes - Koch, A (Refugee Studies Centre, University of Oxford, 2013)
In recent years, ‘assisted voluntary return’ (AVR) schemes have spread across Europe and the Western industrialised world. While AVR is clearly preferable to deportation, NGOs and academics alike have criticised these schemes for being misleadingly labelled and lacking genuine voluntariness.